Supervision and Control of Sharia Banking in Indonesia: The Central Role of the Financial Services Authority (OJK) in Sharia Governance - Hafidza Sanshia Arum; Muhammad Fadhli; Nurnasrina (MUI Kota Pekanbaru, 2025)
The supervision and control of Islamic banking is a fundamental element in maintaining compliance with Islamic principles while ensuring the stability and sustainability of the Islamic finance industry in Indonesia. The rapid development of Islamic banking, fueled by digital innovation and the complexity of financial products, demands a supervisory system that is not only normative, but also adaptive and integrated. This study aims to comprehensively analyze the supervision and control mechanism of Islamic banking in Indonesia and identify the main challenges in its implementation. The research method used is a qualitative approach with a descriptive-analytical design through a literature study of regulations, sharia fatwas, official reports, and relevant scientific literature. Data analysis was carried out using content analysis techniques to assess the alignment between regulatory frameworks, supervisory practices, and sharia governance principles. The results of the study show that Indonesia already has a strong regulatory foundation through Law Number 21 of 2008, the role of the Financial Services Authority, the National Sharia Council-Indonesian Ulema Council, and the Sharia Supervisory Board. However, the effectiveness of supervision still faces challenges in the form of variations in DPS competencies, the lack of optimal harmonization between fatwas and technical regulations, limitations in sharia internal audits, and supervisory readiness in the face of digitalization and sharia fintech. This research emphasizes the need to strengthen sharia governance through improving the quality of human resources, integrating risk-based and technology-based supervision, and more effective institutional coordination to maintain the integrity and competitiveness of Islamic banking in Indonesia.